3-[2-(2,3-Dioxoindolin-1-yl)ethyl]-1,3-oxazolidin-2-one - Al Subari, A.; Bouhfid, R.; Zouihri, H.; Essassi, E.M.; Ng, S.W. (International Union of Crystallography, 2010)
In the title compound, C(13)H(12)N(2)O(4), the almost planar (r.m.s. deviation = 0.012 angstrom) dioxoindolinyl unit and the envelope-shaped oxazolidine ring (with the methylene C atom bonded to the N atom as the flap) are linked by a -CH(2)-CH(2)-bridge, in which the N-C-C-N unit adopts a gauche conformation [torsion angle = 62.7 (2)degrees].